Cross-kingdom comparison of the developmental hourglass. (August 2017) - Drost, Hajk-Georg; Janitza, Philipp; Grosse, Ivo; Quint, Marcel
Highlights: Developmental hourglass patterns are not specific for animals. In plants, developmental hourglass patterns are associated with embryogenesis and post-embryonic phase transitions. Morphological and transcriptomic patterns can be uncoupled. The organizational checkpoint hypothesis proposes that developmental reprogramming inevitably results in evolutionarily conserved transition periods. Abstract : The developmental hourglass model has its foundations in classic anatomical studies by von Baer and Haeckel. In this context, even the conservation of animal body plans has been explained by evolutionary constraints acting on mid-embryogenic development. Recent studies have shown that developmental hourglass patterns also exist on the transcriptomic level, mirroring the corresponding morphological patterns. The identification of similar patterns in embryonic, post-embryonic, and life cycle spanning transcriptomes in plant and fungus development, however, contradict the notion of a direct coupling between morphological and molecular patterns. To explain the existence of hourglass patterns across kingdoms and developmental processes, we propose the organizational checkpoint model that integrates the developmental hourglass model into a framework of transcriptome switches.